ҲИСОБЛАШ УСУЛЛАРИ ФАНИ МАВЗУЛАРИНИ ПОРТФОЛИО АСОСИДА ЁРИТИШ ОРҚАЛИ ТАЛАБАНИ ЎЗ УСТИДА ИШЛАШ КЎНИКМАЛАРИНИ ШАКЛЛАНТИРИШ - Тошбоев, С.М. (SCIENCE and SOCIETY, 2022)
This article provides information on the application of one of the modern innovative methods of teaching students the portfolio method in lectures and practical classes of the course "Computational Methods".